2013
DOI: 10.7314/apjcp.2013.14.12.7701
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Granisetron-Based versus Standard Antiemetic Regimens in Low-Emetogenic Chemotherapy: A Hospital-based Perspective from Malaysia

Abstract: Background: In a prospective cohort study of antiemetic therapy conducted in Malaysia, a total of 94 patients received low emetogenic chemotherapy (LEC) with or without granisetron injections as the primary prophylaxis for chemotherapy-induced nausea and vomiting (CINV). This study is a retrospective cost analysis of two antiemetic regimens from the payer perspective. Materials and Methods: This cost evaluation refers to 2011, the year in which the observation was conducted. Direct costs incurred by hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Although the two antiemetic combinations didn't show any significant difference in the prevention of CINV there was considerable difference in the terms of their costs. The combination including granisetron was almost ten times more expensive compared to one with ondansetron during five days of antiemetic treatment, similarly to the study done in Malaysia 23 . The study showed that both antiemetic combinations (Ondansetron or Granisetron) were effective to prevent CINV but the control was better in acute compared to the delayed phase.…”
Section: Discusssionsupporting
confidence: 56%
“…Although the two antiemetic combinations didn't show any significant difference in the prevention of CINV there was considerable difference in the terms of their costs. The combination including granisetron was almost ten times more expensive compared to one with ondansetron during five days of antiemetic treatment, similarly to the study done in Malaysia 23 . The study showed that both antiemetic combinations (Ondansetron or Granisetron) were effective to prevent CINV but the control was better in acute compared to the delayed phase.…”
Section: Discusssionsupporting
confidence: 56%
“…Adding a 5-HT 3 antagonist to single-agent therapy with dexamethasone or metoclopramide is not cost-effective in this setting. 46 …”
Section: Discussionmentioning
confidence: 99%
“…However, the primary regimen often has to be adjusted or even discontinued due to adverse events, with the chemotherapy-induced nausea and vomiting (CINV) being the most common one, which not only greatly increases the economic burden (Keat and Ghani, 2013) but also produces dehydration, electrolyte disturbance, sub-nutrition, anorexia, weight loss, hypodynamia, sleep deficit, esophageal laceration, and massive hemorrhage, which seriously reduce patients' quality of life (QoL) and are even life-threatening. These limitations hamper the progress of chemotherapy (Hassan and Yusoff, 2010;Uchino et al, 2012;Janelsins et al, 2013).…”
Section: Olanzapine For Preventing Nausea and Vomiting Induced By Modmentioning
confidence: 99%